2017
DOI: 10.1097/moo.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric nasal surgery: timing and technique

Abstract: Pediatric nasal surgery prior to puberty is not only safe, but may prevent facial deformity in certain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
16
1
1
Order By: Relevance
“…This is in contrast with the findings of a recent retrospective review of 43 preadolescent children (defined as males <16 years, females <14 years) who received septoplasty that found that 0 of these patients required revision procedures (1). Other published studies report similarly favorable long-term outcomes in this population (4,5). Similarly, a review of pediatric nasal surgery has demonstrated that conservative and limited nasal surgery with careful preservation of septal structure may be safely performed in the pediatric population with little longterm impact on nasofacial growth (16).…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…This is in contrast with the findings of a recent retrospective review of 43 preadolescent children (defined as males <16 years, females <14 years) who received septoplasty that found that 0 of these patients required revision procedures (1). Other published studies report similarly favorable long-term outcomes in this population (4,5). Similarly, a review of pediatric nasal surgery has demonstrated that conservative and limited nasal surgery with careful preservation of septal structure may be safely performed in the pediatric population with little longterm impact on nasofacial growth (16).…”
Section: Discussioncontrasting
confidence: 60%
“…The septal cartilage plays a major role in growth and development of the midface. Specifically, the sphenodorsal zone increases the length and height of the nasal bones, while the sphenospinal zone increases maxilla outgrowth (4,5). As a result, surgeons have adopted a cautious attitude towards correction of nasal septal deformities in the pediatric population, often electing to wait until puberty to perform the procedure (3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations